The correlation between pentraxin-3, matrix metalloproteinase-9, and estimated glomerular filtration rate in patients with chronic kidney disease - Harun, Harnavi; Dewi, Amelia Fitria; Amelia, Rinita (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Background: Chronic kidney disease (CKD) is diagnosed when there is a sustained decrease in the estimated glomerular filtration rate (EGFR) over a period of more than 3 months. While Pentraxin-3 (PTX-3) and Matrix Metalloproteinase-9 (MMP-9) levels increase during the acute phase of the kidney injury, chronic conditions often exhibit alteration in the epithelial mesenchymal transition (EMT).Objectives: This study aimed to elucidate the correlation between serum PTX-3, MMP-9, and eGFR in patients with CKD. Method: Thirty hypertensive patients with CKD stages 3, 4, and 5, aged between 16 and 65 years, were enrolled in the study (15 males and 15 females). Diagnosis of CKD was based on the 2012 Kidney Disease Improving Global Outcomes (KDIGO) criteria, utilizing serum creatinine, and CKD-epidemiology Collaboration (CKD-EPI) estimates. Subsequently, serum MMP-9 and PTX-3 levels were quantified. Result: Patients with CKD exhibited significantly higher serum levels of PTX3 and MMP9. Furthermore. a significant negative connection between PTX-3, MMP-9, and EGFR was observed. Additionally, CKD patients displayed a correlation between PTX-3 and MMP-9 concentrations.Conclusion: Plasma levels of PTX-3 and MMP-9 serve as unique, promising, and important markers that contribute to the pathogenesis of CKD.